Influence of Filler Content on the Mechanical, Thermal, Moisture Absorption, and Biodegradability Properties of Bionanocomposite with Cellulosic Fibers Derived from Delonix Regia Fruits - Kalpit Kaurase; Dalbir Singh (Mechanics of Advanced Composite Structures)
Cellulose is one of the most widely used and widely available materials on the planet, and it has been used for centuries in a wide range of applications. In this paper, a new source of cellulose delonix regia fruits has been explored for the extraction of cellulose at the micro and nanoscale. Cellulose is isolated from the raw delonix regia fruits by sub-sequential chemical methods such as pulping, bleaching, delignification, and acid hydrolysis.  PVA/CMF and PVA/CNF composites are prepared by the solvent casting process with 1, 3, 5, 7, and 9 percentages of filler concentration. Mechanical, thermal, morphological, moisture absorption, and biodegradability properties of pure PVA, PVA/CMF, and PVA/CNF composite at different filler concentrations were evaluated using mechanical testing (tensile, flexural, and impact), TGA-DTG, SEM, moisture absorption test and soil burial test respectively. The SEM results showed that at increased filler content concentrations, signs of agglomeration began to occur, and the overall performance of the resulting composite material degraded due to which filler addition should be limited to less than 7wt%. Tensile, flexural, and impact test results revealed that nano-fillers performed better than micro-fillers, and the best performance is obtained with filler content below 7%. The degradation temperature of composites with filler content improved dramatically, according to TGA and DTG curves, and composites with nano-fillers had greater thermal stability than composites with micro-fillers. The inclusion of filler content reduced the tendency of composite materials to absorb moisture and the resulting composite materials had enough biodegradation rate together with higher lifetime and performance, according to the findings of the biodegradability test and moisture absorption test.